2021
DOI: 10.1021/acs.jafc.0c06534
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Ameliorates Di(2-ethylhexyl) Phthalate-Induced Pyroptosis in Spleen via Suppression of Classic Caspase-1/NLRP3 Pathway

Abstract: Lycopene (Lyc) as a natural antioxidant has attracted widespread attention. Di­(2-ethylhexyl) phthalate (DEHP) can cause serious spleen injury in animals via the environment and food chain. For investigation of whether Lyc could alleviate DEHP-exerted pyroptosis in spleen through inhibiting the Caspase-1/NLRP3 pathway activation, 140 male mice were randomly divided into 7 groups: control group, vehicle control group, Lyc group (5 mg/kg BW/day), DEHP-exposed group (500 or 1000 mg/kg BW/day, respectively), and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 57 publications
1
15
1
Order By: Relevance
“…In our study, the relative protein expression of procaspase-8 and cleaved caspase-3 was detected by western blotting analysis, while TUNEL staining was employed to quantify apoptosis levels. Our results indicate that LYC or DAPT pretreatment can downregulate the CS-induced increases of procaspase-8 and cleaved caspase-3, which is consistent with previous investigations observing that LYC alleviated spleen apoptosis caused by di­(2-ethylhexyl)­phthalate and AFB 1 . , Collectively, these findings demonstrate that LYC can relieve chronic stress-induced death receptor pathway-mediated apoptosis of rat splenocytes by inhibiting the Notch pathway.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the relative protein expression of procaspase-8 and cleaved caspase-3 was detected by western blotting analysis, while TUNEL staining was employed to quantify apoptosis levels. Our results indicate that LYC or DAPT pretreatment can downregulate the CS-induced increases of procaspase-8 and cleaved caspase-3, which is consistent with previous investigations observing that LYC alleviated spleen apoptosis caused by di­(2-ethylhexyl)­phthalate and AFB 1 . , Collectively, these findings demonstrate that LYC can relieve chronic stress-induced death receptor pathway-mediated apoptosis of rat splenocytes by inhibiting the Notch pathway.…”
Section: Discussionsupporting
confidence: 92%
“…14 Additionally, numerous studies have revealed the novel role of Lyc in decreasing the toxic effect of environmental risk factors. 18–20 Previous studies indicated that Lyc consumption protected the spleen, heart and kidney from ATZ exposure due to its antioxidant properties. 4,18 However, the protective role of Lyc in ameliorating ATZ-induced thymic injury is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…14 It will disrupt the health of humans and animals through the food chain. 10,15,16 Numerous studies have shown that the exposure of DEHP could cause harm to the liver, 17 spleen 18 and testis 19 in mice. A previous study showed that it would disrupt the heart rate variability and cardiovascular reactivity after DEHP exposure.…”
Section: Introductionmentioning
confidence: 99%